A peculiar Lithuanian particle mat or Mat ją bala, irgi mat dalelytė! - Panov, Vladimir; Trakymaitė, Ringailė (Vilnius University Open Series, 2021)
In this paper, we discuss the morphosyntactic properties and the functional contribution of the discourse-structuring element mat in Lithuanian, which was largely overlooked in previous research. We demonstrate that in each function mat is associated with peculiar morphosyntactic behaviour. We argue that it is the construction in which it occurs as a whole that bears meaning, rather than mat as a lexical unit on its own. In our analysis, we invoke insights and some apparatus of Construction Grammar approaches, which fit well with our observations in their focus on non-compositional aspects of linguistic structure.